Exploring the Utilization of ICT in Learning and Teaching of English at Undergraduate Stage: A Case Study of Public Sector Universities in Baluchistan - Mah Naz; Zahid Ali; Khursheed Ahmad (University of Chitral Journal of Linguistics and Literature, 2022)
The utilization of Information and Communication Technologies (ICTs) represents an alternative approach to learning and teaching English at the university level. This method has the potential to enhance the academic standard by adopting a learner-centered approach, which has significantly contributed to generating interest in English language instruction. The purpose of this study is to conduct a survey on the use of ICTs in language classrooms. The research explores the differences between traditional and modern modes of instruction from the instructors' perspectives. The study employs a quantitative approach, utilizing online five-point Likert scale questionnaires to collect data. Based on the responses received, the findings reveal that technology has played a significant role in the teaching and learning of English at the university level. It has demonstrated the ability to improve the teaching process while simultaneously enhancing the learning experience. As such, the study recommends the provision of adequate technical facilities to universities in the province of Baluchistan to enable the proper execution of technology in the learning and teaching process. Additionally, suitable training sessions must be conducted to ensure the efficient use of technological gadgets for instructional purposes, thereby creating a better platform towards the learning process.Keywords: Baluchistan, English, ICT, learn, teach, university